THE EFFECTIVENESS OF ONLINE PLATFORMS IN DEVELOPING SPEAKING SKILLS IN EFL CLASSROOMS - Kanatbayeva Aktoty Talgatovna; Sembaeva Zhanagul Kostanaykyzy (Foundations and Trends in Modern Learning, 2025)
This research examines the impact of integrating an online platform - specifically authentic video content from TED Talks - on the development of speaking skills in an English as a Foreign Language (EFL) classroom. A quasi-experimental design was implemented with 40 first-year university students in Kazakhstan, divided into an experimental group using TED Talk-based activities and a control group following traditional textbook-based instruction. Over a four-week period, the experimental group engaged with curated TED Talks and related speaking tasks, while both groups completed pre- and post-intervention speaking tests and the experimental group also answered a 25-item survey. The results show that the experimental group’s post-test speaking scores improved significantly more than the control group’s (mean gain ≈+3.6 vs +0.7, p < 0.001). Survey data indicated that about 55% of students preferred the TED-based approach over traditional materials, and over 85% reported gains in speaking confidence, vocabulary, and motivation. Qualitative feedback highlighted benefits such as exposure to authentic language and increased engagement, alongside challenges like fast speech and unfamiliar vocabulary. The findings suggest that online platforms offering authentic content can effectively enhance EFL learners’ speaking skills when combined with supportive pedagogical strategies. The research concludes with practical recommendations for incorporating such platforms to foster oral communication skills in language classrooms